Advances for pharmacological activities of Polygonum cuspidatum - A review - Ke, Jia; Li, Meng-Ting; Xu, Shuyang; Ma, Jianpeng; Liu, Ming-Yuan; Han, Yan (Pharmaceutical biology, 2023)
Polygonum cuspidatum Sieb. et Zucc (Polygonaceae), the root of which is included in the Chinese Pharmcopoeia under the name 'Huzhang', has a long history as a medicinal plant and vegetable. Polygonum cuspidatum has been used in traditional Chinese medicine for the treatment of inflammation, hyperlipemia, etc. This article reviews the pharmacological action and the clinical applications of Polygonum cuspidatum and its extracts, whether in vivo or in vitro. We also summarized the main phytochemical constituents and pharmacokinetics of Polygonum cuspidatum and its extracts. The data were retrieved from major medical databases, such as CNKI, PubMed, and SinoMed, from 2014 to 2022. Polygonum cuspidatum, pharmacology, toxicity, clinical application, and pharmacokinetics were used as keywords. The rhizomes, leaves, and flowers of Polygonum cuspidatum have different phytochemical constituents. The plant contains flavonoids, anthraquinones, and stilbenes. Polygonum cuspidatum and the extracts have anti-inflammatory, antioxidation, anticancer, heart protection, and other pharmacological effects. It is used in the clinics to treat dizziness, headaches, traumatic injuries, and water and fire burns. Polygonum cuspidatum has the potential to treat many diseases, such as arthritis, ulcerative colitis, asthma, and cardiac hypertrophy. It has a broad range of medicinal applications, but mainly focused on root medication; its aerial parts should receive more attention. Pharmacokinetics also need to be further investigated.